2019
DOI: 10.1002/mus.26749
|View full text |Cite
|
Sign up to set email alerts
|

Loss of appetite in amyotrophic lateral sclerosis is associated with weight loss and decreased calorie consumption independent of dysphagia

Abstract: Background: In the current study, we aimed to determine normative values for muscle thickness and fasciculation prevalence in healthy subjects.Methods: We performed a prospective study from October to December 2018 in 65 healthy subjects. All subjects underwent quantitative sonographic evaluation of muscle thickness and fasciculation prevalence in the following 8 muscles: Biceps brachii, abductor pollicis brevis, first dorsal interosseous, abductor digiti minimi, quadriceps, tibialis anterior, extensor digitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…Although various studies have suggested that hypermetabolism could lead to loss of body weight in patients with ALS, a recent study by Steyn et al [62] reported no significant differences in body weight between hypermetabolic and normometabolic ALS patients, suggesting that other mechanisms such as loss of appetite and malnutrition may contribute to body weight loss. Indeed, loss of appetite has been shown in a subset of patients with ALS, which contributes to reduced food intake [63][64][65]. This is in agreement with studies that show malnutrition in patients with ALS.…”
Section: Disturbed Energy Homeostasis In Patients With Alssupporting
confidence: 85%
“…Although various studies have suggested that hypermetabolism could lead to loss of body weight in patients with ALS, a recent study by Steyn et al [62] reported no significant differences in body weight between hypermetabolic and normometabolic ALS patients, suggesting that other mechanisms such as loss of appetite and malnutrition may contribute to body weight loss. Indeed, loss of appetite has been shown in a subset of patients with ALS, which contributes to reduced food intake [63][64][65]. This is in agreement with studies that show malnutrition in patients with ALS.…”
Section: Disturbed Energy Homeostasis In Patients With Alssupporting
confidence: 85%
“…However, a declining pattern of haemoglobin after diagnosis was associated with a higher mortality, although the association was borderline significant. This finding lends further support to the important role of nutritional status in the survival of ALS patients, which is multifactorial and influenced by metabolism [16], energy intake, ease of breath, and appetite [17][18][19].…”
Section: Discussionsupporting
confidence: 70%
“…However, given that hypermetabolism has not been shown to be associated with weight loss in human ALS ( Steyn et al , 2018a ), these divergent observations between ALS mice and patients suggest that multiple factors are likely to contribute to weight loss in patients with ALS. These include reduced capacity to meet energy requirements ( Ngo et al , 2017 ) [including loss of appetite resulting in loss of fat mass ( Ngo et al , 2019 ; Mezoian et al , 2020 )], as well as neurogenic wasting ( Al-Sarraj et al , 2014 ).…”
Section: Discussionmentioning
confidence: 99%